KEMAMPUAN KEPRIBADIAN PEMIMPIN SEKOLAH MASA KINI PADA MOTIVASI KINERJA GURU - Aceng Ali Nurdin; Sopyan Iskanda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The personality abilities of principals currently play an important role and contribute to the teacher’s motivation to make schools successful and superior. The purpose of the study discussed in this article was to describe the personality abilities of school leaders in the motivation for teacher performance at SDN 1 Bojong in West Bandung. The study was conducted by using a qualitative approach. The method used was descriptive qualitative. The type of research used is multi-site. The subject of the study involved the principal and teacher at school. Data collection techniques were carried out through observation, in-depth interviews, and analysis of documentary evidence. The results of the study were (1) the school principal has good exemplary behaviour, (2) the school principal has an honest attitude, sincerity, commitment, and integrity, (3) the school principal was open in carrying out the main tasks and functions, (4) the school principal was able to control himself in dealing with problems, (5) the school principal was able to participate in community social activities, (6) the school principal was considerate and concerned about the interests of others, and (7) the school principal was able to manage relations with outside parties. The supporting factor was the existence of teacher independence because the high teacher integrity influenced the development of the school. The inhibiting factor was the presence of teachers who were not yet proficient in IT. A mindset of the school principal has been embedded and a good personality, able to show, implemented, and practiced attitudes as a leader at school, and an improvement of teacher performance.